Morphogenesis and evolution. - Thomson, Keith Stewart (Oxford University Press, USA, 1988)
1. Introduction. 2. Theory, Reduction, and Hierarchy. 3. Development: Pattern and Process. 4. Early Pattern Formation. 5. Example: Early Pattern Formation in Amphibia. 6. Later Pattern Formation: Morphogenesis. 7. Some General Properties of Morphogenetic Systems. 8. Patterns of Evolution. 9. Morphogenesis and Evolution.